2015
DOI: 10.3390/ijms160715761
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Short Physical Exercise Intervention on Patients with Multiple Sclerosis (MS)

Abstract: Background: The aim of this prospective randomized controlled trial was to investigate if a short-term endurance or combined endurance/resistance exercise program was sufficient to improve aerobic capacity and maximum force in adult patients (18–65 years) with multiple sclerosis (MS). Methods: All patients performed a three-month exercise program consisting of two training sessions per week, lasting 40 min each, with moderate intensity. All patients had a maximum value of 6 (low to moderate disability) on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 39 publications
1
35
0
3
Order By: Relevance
“…[11][12][13][14][15] While exercise training has been shown to increase VO 2peak in people with MS, measures of whole-body oxygen consumption are influenced by central and peripheral factors and do not directly evaluate changes in muscle-specific oxidative capacity. [16][17][18] Muscle oxidative capacity, or the capacity to produce energy through aerobic pathways, is directly related to muscle endurance, and, therefore, may be important in interventions aiming to improve endurance in people with MS. A recent study demonstrated improved muscle metabolism with electrical stimulation training in persons with MS, 19 but there is little evidence to support the use of voluntary exercise in interventions aimed at improving muscle oxidative capacity.…”
Section: Muscle Oxidative Capacitymentioning
confidence: 99%
“…[11][12][13][14][15] While exercise training has been shown to increase VO 2peak in people with MS, measures of whole-body oxygen consumption are influenced by central and peripheral factors and do not directly evaluate changes in muscle-specific oxidative capacity. [16][17][18] Muscle oxidative capacity, or the capacity to produce energy through aerobic pathways, is directly related to muscle endurance, and, therefore, may be important in interventions aiming to improve endurance in people with MS. A recent study demonstrated improved muscle metabolism with electrical stimulation training in persons with MS, 19 but there is little evidence to support the use of voluntary exercise in interventions aimed at improving muscle oxidative capacity.…”
Section: Muscle Oxidative Capacitymentioning
confidence: 99%
“…Tab. 4.7) inklusive der Therapie auslösender Ursachen (wie gestörter Nachtschlaf bei Blasenstörungen, Unterfunktion der Schilddrüse) in Frage (Pateijdl 2015 tik auswirkt (Andreasen et al 2011 (Kerling et al 2015). Aufgrund der multifaktoriellen Ätiologie der Fatigue ist eine Kombination verschiedener Verfahren häufig am vielversprechendsten (DGN 2014;Patejdl et al 2015).…”
Section: Symptombezogene Inanspruchnahmeunclassified
“…20 However, weakness and atrophy are usual consequences of physical inactivity which may also cause physical impairment and increased disease severity. 21 In fact, recent researches have addressed the beneficial role of physical exercise for MS patients 1,4 , and a recent study has proven exercise to be beneficial to MS patients, decreasing fatigue and increasing quality of life 22 , and another study by Briken et al 23 also states that exercise may be beneficial for physical fitness and cognition of MS patients. Furthermore, an elegant review by Motl and Pilutti 1 states that exercise training has positive effects on muscle strength, aerobic capacity, walking performance, fatigue, gait, balance and quality of life of MS patients.…”
Section: Introductionmentioning
confidence: 98%